What distinguishes life satisfaction from emotional wellbeing? - Fors Connolly, Filip; Gärling, Tommy (Frontiers in Psychology, 2024)
The aim of this registered report is to investigate how the core components of subjective wellbeing, Life Satisfaction (LS) and Emotional Well-Being (EWB), differ with respect to their relationship to antecedent factors. Seven factors are proposed that have been found in previous research to antecede LS and EWB. Social Comparisons, Meaningfulness, Economic/Social Resources, and Opportunities are hypothesized to correlate more closely with LS than EWB, while Time Use, Hassles/Uplifts, and Neuroticism are hypothesized to correlate more strongly with EWB than LS. A combined online and paper-and-pencil survey was administered to a representative sample of 974 Swedish citizens aged 15 years or older. LS and EWB were measured by self-report methods that have been developed and used in previous research. Index measures were constructed from self-reports of each antecedent factor by means of ratings on two scales developed in this study. Multivariate regression and relative weight analyses confirmed two of the hypotheses in showing that Economic/Social Resources and Opportunities were significantly more strongly related with LS than EWB. Of those hypothesized to correlate more strongly with EWB than LS, support was obtained for Neuroticism. Social Comparisons, Meaningfulness, Time Use, and Hassles/Uplifts did not have different relationships with LS and EWB. The results confirm that to some extent antecedent factors are differentially associated with LS and EWB, thus contributing to a better understanding of the antecedents of the cognitive and affective components of subjective well-being. Future research should further explore the mechanisms underlying these different relationships as well as moderators and mediators of the relationships.